Dimethyldioctadecylanimonium bentonite immobilized magnetic chitosan nanoparticles as an efficient adsorbent for vortex‐assisted magnetic dispersive micro‐solid‐phase extraction of celecoxib from human breast milk, plasma and urine samples. (27th May 2020) - Majidi, Seyedeh Maedeh; Hadjmohammadi, Mohammad Reza
Abstract: A polymer/layered silicate composite based on dimethyldioctadecylanimonium bentonite/chitosan magnetic nanoparticles was synthesized and characterized by field emission transmission electron microscopy, X‐ray diffraction and Fourier transform infrared spectrometry. The prepared nanocomposite was used to isolate and preconcentrate celecoxib from human breast milk, urine and plasma samples. In this method, dimethyldioctadecylanimonium bentonite increases the accessibility of binding sites and adsorption capacity by high microporosity and large surface area, that has been realized for the first time in a magnetic chitosan nanoparticle support. A fractional factorial design was utilized for screening the experimental parameters. The effective parameters were then optimized by Box–Behnken design. Under the optimized conditions, the developed method exhibited wide linear ranges of 5–500 μg L −1 for plasma and urine and 10–500 μg L −1 for breast milk samples with satisfactory recoveries in the range of 96.7–99.0%. Limit of detection and quantification of celecoxib were in the ranges 0.3–3.2 and 0.99–10.56, respectively. The enrichment factors were obtained in the ranges 64.5–66.0, while precisions were <3.7%.